Effect of Major Illness Insurance on Vulnerability to Poverty: Evidence From China - Zheng, Lili; Peng, Lijin (Frontiers in Public Health, 2021)
Disease is the primary cause of poverty in China. Health insurance is an essential mechanism for managing health risks and addressing the risk of financial loss. Using data from the China Family Panel Studies (CFPS) waves from 2010, 2021, 2012, 2014, and 2016, this study develops a random forest method to assess households’ vulnerability to poverty and then examines the impact of major illness insurance on vulnerability to poverty by focusing on the rollout period of a major illness insurance scheme. The research also examines the impact of increased major illness insurance coverage on poverty reduction by focusing on the change from low- to high-coverage health insurance. The findings indicate that major illness insurance and improvements in the degree of coverage significantly reduce vulnerability to poverty. In addition, major illness insurance is found to alleviate the vicious cycle of poverty and disease through the mechanism of increasing household income, and its effect has strengthened over time. Compared to other poverty reduction policies, major illness insurance has a greater influence on poverty alleviation.